The standard posture is a myth: a scoping review - Martin E. Barra-López (Medical Journals Sweden, 2024)
Background: The standard posture described in Kendall's manual is commonly used for postural assessment. However, no bibliographic reference was provided to support its use. Objective: To identify the original source and the procedure followed for the design of that posture and to compare it with current literature on the subject. Methods: In accordance with the PRISMA Extension for Scoping Reviews recommendations, PubMed and Scopus were searched using the terms "standing posture", "plum line," and "gravity line". Publications in English, French, German, or Spanish that referred to posture in adults without pathology were included. Results: Six articles and 3 books were included in the final analysis. An identical posture to that described in Kendall's manual was identified in an early 19th-century work carried out with the unrealistic objective of maintaining static bipedal standing without muscular support, and including several anatomical misconceptions. Furthermore, the "ideal alignment" described in Kendall's manual does not correspond to the actual line of gravity, the comfortable posture, or natural postural compensations due to age, gender, or race. Conclusion: The utilization of this standard to ascertain postural deficiencies is not supported by current evidence and may result in numerous false positives, particularly in the elderly.